Exploring the effects of cannabidiol encapsulation in liposomes on their physicochemical properties and biocompatibility - Inga Jurgelane; Karina Egle; Andra Grava; Dana Galkina; Margarita Brante; Maksims Melnichuks; Marite Skrinda-Melne; Girts Salms; Arita Dubnika (Drug Delivery)
Cannabidiol (CBD) is recognized for its therapeutic properties in various conditions. However, CBD’s limited water solubility and sensitivity to environmental stresses hinder its efficacy and bioavailability. Encapsulation in drug delivery systems, particularly liposomes, offers a promising solution. This study aims to prepare CBD-containing liposomes using commercially used lipids distearoyl phosphatidylcholine (DSPC) and dipalmitoyl phosphatidylcholine (DPPC), and 1,2 distearoyl-sn-glycero-3 phosphoethanolamine-N-[carbonyl-amino(polyethylene glycol)-4300] (ammonium salt) (DSPE-PEG) and to perform in vitro studies – cell viability and CBD release. Liposomes were synthesized using thin-film hydration method, and characterized by Fourier-transform infrared (FT-IR) spectroscopy, dynamic light scattering (DLS), and scanning transmission electron microscopy (STEM). DLS analysis revealed that CBD incorporation reduced liposome size by 23–53%, depending on the liposomes. Encapsulation efficiency followed the order: DPPC CBD (63%) < DSPC CBD (74%) < DSPC DPPC CBD (81%) < DSPC DSPE-PEG CBD (87%). CBD release profiles indicated that DPPC CBD liposomes released the highest CBD amount initially, while DSPC DSPE-PEG CBD exhibited sustained release, achieving 79% release over 504 h. In vitro cell viability tests showed that blank liposomes were non-cytotoxic. However, CBD-loaded liposomes significantly reduced cell viability for defined type of CBD containing liposomes. The inclusion of DSPE-PEG improved encapsulation efficiency and liposome stability, making DSPC DSPE-PEG CBD liposomes more suitable for long-term CBD release. Compared to other studies, encapsulation of CBD in liposomes enhances its bioavailability, allowing lower concentrations of CBD to be directly delivered to cells, resulting in observable changes in cell viability.